Strong correlation of maximal squat strength with sprint performance and vertical jump height in elite soccer players - Wisloff, U.; Castagna, C.; Helgerud, J.; Jones, R.; Hoff, J. (British Journal of Sports Medicine, 2004)
Background: A high level of strength is inherent in elite soccer play, but the relation between maximal strength and sprint and jumping performance has not been studied thoroughly.